Silencing of ATG6 and ATG8 promotes increased levels of triacylglycerol (TAG) in the fat body during prolonged starvation periods in the Chagas disease vector Rhodnius prolixus. (December 2020) - Santos-Araujo, Samara; Bomfim, Larissa; Araripe, Luciana O.; Bruno, Rafaela; Ramos, Isabela; Gondim, Katia C.
Abstract: Rhodnius prolixus is an obligatorily hematophagous insect known as an important vector of Chagas disease. Autophagy is a conserved cellular mechanism that acts in response to nutrient starvation, where components of the cytoplasm are sequestered by a double membrane organelle, named autophagosome, which is targeted to fuse with the lysosome for degradation. Lipophagy is the process of lipid degradation by selective autophagy, where autophagosomes sequester lipid droplets and degrade triacylglycerol (TAG) generating free fatty acids for β-oxidation. Here, two essential genes of the autophagic pathway, Atg6/Beclin1 ( RpAtg6 ) and Atg8/LC3 ( RpAtg8 ), were silenced and the storage of lipids during starvation in Rhodnius prolixus was monitored. We found that RNAi knockdown of both RpAtg6 and RpAtg8 resulted in higher levels of TAG in the fat body and the flight muscle, 24 days after the blood meal, as well as a larger average diameter of the lipid droplets in the fat body, as seen by Nile Red staining under the confocal fluorescence microscope. Silenced starved insects had lower survival rates when compared to control insects. Accordingly, when examined during the starvation period for monitored activity, silenced insects had lower spontaneous locomotor activity and lower forced flight rates. Furthermore, we found that some genes involved in lipid metabolism had their expression levels altered in silenced insects, such as the Brummer lipase (down regulated) and the adipokinetic hormone receptor (up regulated), suggesting that, as previously observed in mammalian models, the autophagy and neutral lipolysis machineries are interconnected at the transcriptional level. Altogether, our data indicate that autophagy in the fat body is important to allow insects to mobilize energy from lipid stores. Graphical abstract: Image 1 Highlights: RpAtg6 or RpAtg8 knockdown results in increased triacylglycerol stores in starving Rhodnius prolixus. Lipid droplets in the fat body of knockdown females are larger. Knockdown insects show decreased locomotor activity and lower starvation survival rates.